2015
DOI: 10.4155/fmc.15.126
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Ceramide Analogs Modified at the 1-Position with Potent Activity Against the Intracellular Growth of Chlamydia Trachomatis

Abstract: The structure-activity relationship presented here defines an important step toward the molecular target of this compound class, which is still elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…All solvents and reagents used were of highest available purity and purchased from typical suppliers. The d -erythro-sphingosine (d18:1), ceramide C18 (d18:1/18), and ceramide C18:1 (d18:1/18:1) used in this study were synthesized according to previous methods developed by the Arenz laboratory 53 . All other lipids were purchased from Avanti Polar Lipids.…”
Section: Methodsmentioning
confidence: 99%
“…All solvents and reagents used were of highest available purity and purchased from typical suppliers. The d -erythro-sphingosine (d18:1), ceramide C18 (d18:1/18), and ceramide C18:1 (d18:1/18:1) used in this study were synthesized according to previous methods developed by the Arenz laboratory 53 . All other lipids were purchased from Avanti Polar Lipids.…”
Section: Methodsmentioning
confidence: 99%
“…pDONR223‐COL4A3BP was a gift from William Hahn & David Root (Addgene plasmid #23569; Johannessen et al, ); primers were obtained from MWG Eurofins. HPA12 used in this study was synthesised according to previous methods developed in our lab (Saied, Banhart, Burkle, Heuer, & Arenz, ; Saied, Diederich, & Arenz, ). BODIPY FL C5‐ceramide complexed to BSA was purchased from Molecular Probes.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, recent studies demonstrated that the sphingoid base sphingosine is also an important first-line defence of healthy airways against Pseudomonas aeruginosa 11 . Recently, a series of ceramide analogs was synthesized and analysed for the growth inhibitory effect on Chlamydia trachomatis 12 . Moreover, several synthetic dihydrosphingosine analogs have been demonstrated to be active against multi-drug resistant strains of Mycobacterium tuberculosis 13 .…”
Section: Introductionmentioning
confidence: 99%